(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2025)
Vertebrate palaeoichnology often aims at the identification of the trackmaker by associating diagnostic features from the known taxa’s skeletal anatomy with its inferred footprint morphology, but deep penetrative tracks and/or deep, detached undertracks (DDU) are providing conflicting morphological/extra-morphological information, bringing into question the initially assumed close anatomical correlation. Penetrative footprints produced in fluvial-dominated deltaic facies from Upper Jurassic Lastres Formation are very frequent in the coastal cliffs of Asturias (N Spain). Some of them consist of non-avian theropod track casts associated with “ornithopod-like” detached undertracks. Some criteria are suggested to distinguish the latter when such an association does not exist. Moreover, we describe an exceptional theropod footprint preserved as a sandstone cast along with its respective deep detached sandstone undertrack (DDSU). The specimen records the foot movement through the sediment, entailing striking morphologic changes in outline along four different levels of depth. The uppermost level 1 shows an apparent stegosaur hind track morphology; level 2 resembles an avian-theropod print; level 3 represents the true non-avian theropod pedal morphology of the trackmaker; the lowermost level 4 corresponds to the deep detached sandstone undertrack (DDSU), which could be interpreted as either a track of a graviportal theropod or an ornithopod-like footprint. In light of this new evidence, it becomes clear that vertebrate ichnotaxonomy should not be based solely on the supposed trackmaker identification. Furthermore, biogeographic and evolutionary studies linked to this core information should be considered unsupported, along with many ichnotaxonomical assignations based on taphonomic processes, such as the case exemplified herein, the Iguanodontipus ichnogenus.